Aristotelian rhetoric and Facebook success in Israel's 2013 election campaign. Issue 2 (13th April 2015) - Samuel-Azran, Tal; Yarchi, Moran; Wolfsfeld, Gadi
Abstract : Purpose: – The purpose of this paper is to contribute to the mapping of the social media discourse involving politicians and their followers during election campaigns, the authors examined Israeli politicians' Aristotelian rhetoric on Facebook and its reception during the 2013 elections campaign. Design/methodology/approach: – The authors examined the Aristotelian rhetorical strategies used by Israeli politicians on their Facebook walls during the 2013 elections, and their popularity with social media users. Findings: – Ethos was the most prevalent rhetorical strategy used. On the reception front, pathos-based appeals attracted the most likes. Finally, the results point to some discrepancy between politicians' campaign messages and the rhetoric that actually gains social media users' attention. Research limitations/implications: – The findings indicate that Israel's multi-party political system encourages emphasis on candidates' credibility (ethos) in contrast to the prevalence of emotion (pathos) in typical election campaigns in two-party systems like the USA. One possible explanation is the competitive nature of elections in a multi-party system where candidates need to emphasise their character and distinct leadership abilities. Practical implications: – Politicians and campaign managers are advised to attend to the potential discrepancy between politicians' output and social media users' preferences, and to the effectiveness of logos-based appeals. Originality/value: – The study highlights the possible effect of the party system on politicians' online rhetoric in social media election campaigns.